Manifestasi seni ukiran kayu kontemporari: Abd Muhaimin bin Hasbollah - Yusniza Mohamed Yusof (Tanjong Malim, 2020)
Manifestasi seni ukiran kayu kontemporari: Abd Muhaimin bin Hasbollah by Yusniza Mohamed Yusof